2012
DOI: 10.6063/motricidade.8(1).238
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do treinamento funcional com cargas sobre a composição corporal: Um estudo experimental em mulheres fisicamente inativas

Abstract: RESUMOO presente estudo objetivou analisar os efeitos do treinamento funcional com cargas (TFC) na composição corporal de mulheres fisicamente inativas. Vinte mulheres (25.70 ± 4.20 anos) foram designadas aleatoriamente para os grupos experimental (GE, n = 10) e controle (GC, n = 10), tendo o GE realizado 12 semanas de TFC, enquanto o GC não recebeu qualquer intervenção. As variáveis antropométricas avaliadas em ambos os grupos foram: massa corporal (MC), estatura, índice de massa corporal (IMC), massa de gord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
5
0
4
Order By: Relevance
“…There is strong evidence that strength training reduces the effects of aging on the neuromuscular system and functional capacity [10][11][12][13][14][15]. Strength training elicits the reduction of adipose tissue [16] and increases muscle mass [17,18], bone density [19], and muscle strength [20,21]. Traditional strength training provides an increase in muscle strength.…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence that strength training reduces the effects of aging on the neuromuscular system and functional capacity [10][11][12][13][14][15]. Strength training elicits the reduction of adipose tissue [16] and increases muscle mass [17,18], bone density [19], and muscle strength [20,21]. Traditional strength training provides an increase in muscle strength.…”
Section: Introductionmentioning
confidence: 99%
“…Although machine-based traditional training (TT) protocols promote several structural adaptations such as increased muscle mass [6], bone mineral density [7], and reduction of adipose tissue [8], there are questions about their ability to transfer to activities of daily living [9]. Serra-Rexach et al [10], reported increase of strength in nonagenarian older adults after eight weeks of TT but no change was observed in the functional standing up and walking test.…”
Section: Introductionmentioning
confidence: 99%
“…Desta forma, a prática de exercício físico apresenta-se como uma potencial medida preventiva para melhorar as variáveis relacionadas ao risco de quedas, entre elas a autonomia funcional, composição corporal, força, equilíbrio, agilidade, qualidade de vida e densidade mineral óssea (NEVES, FORTALEZA, ROSSI, DINIZ, PICOLO, BUONANI et al, 2015;ROCHA et al, 2017;PEREIRA, MEDEIROS, SANTOS, OLIVEIRA, ANICETO, JÚNIOR et al, 2012. O exercício físico regular e bem orientado, surge como uma medida não farmacológica, eficaz para atenuar ou reverter os efeitos deletérios do envelhecimento (PINTO, 2014;PERFEITO E ROCHA, 2016;CAMACHO, 2018).…”
Section: Francisco José Félix Saavedraunclassified